Penerapan Asas Itikad Baik Dalam Pelaksanaan Perjanjian Jual Beli Tanah - Ahmad Riansyah; Roihan; Riski Rahmadhan; M. Willy Pratama; Ricky Nopriyadi (Consensus : Jurnal Ilmu Hukum, 2022)
The principles of faith in civil law must apply to any agreement, whether between individuals and individuals or between individuals with legal bodies. In paragraph 3 of article 1338 of the Covenant, referred to in this document as the "Covenant", it is stated that "good will" in this sense means acting in the right way morally. Normative law research also gathers secondary law sources. A company should not harm others or exploit others for personal gain is a topic of talk about faith. To conclude, in the case of sale of land, the application of the credentials occurs at the time of entry into force of the law or when the rights and obligations established in the legal relationship are implemented.Any party to a treaty must do so in good faith, according to article 1338, paragraph 3.